2020
DOI: 10.3390/ijms21062088
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Potential Regulatory Mechanisms of Melanin Synthesis in Harmonia axyridis

Abstract: Melanization is a common phenomenon in insects, and melanin synthesis is a conserved physiological process that occurs in epidermal cells. Moreover, a comprehensive understanding of the mechanisms of melanin synthesis influencing insect pigmentation are well-suited for investigating phenotype variation. The Asian multi-colored (Harlequin) ladybird beetle, Harmonia axyridis, exhibits intraspecific polymorphism based on relative levels of melanization. However, the specific characteristics of melanin synthesis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…6). Consistent with this result, dysfunction of TH also causes deformed and separated elytra 3, 7, 13 …”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…6). Consistent with this result, dysfunction of TH also causes deformed and separated elytra 3, 7, 13 …”
Section: Discussionsupporting
confidence: 70%
“…Biochemically, the cuticle tanning in most insects results from a combination of melanins and sclerotins 3,5–12 . These compounds are produced from tyrosine precursor by a branched biochemical pathway 13 .…”
Section: Introductionmentioning
confidence: 99%
“…A previous study demonstrated that the elytra color pattern variation in H. axyridis is a melanization phenomenon in the cuticle ( True, 2003 ). In our previous studies, we have confirmed that dopamine melanin synthesis is the primary pathway in the elytra of H. axyridis ( Chen et al, 2019b ; Xiao et al, 2020 ). Meanwhile, the aspartate- β -alanine-NBAD pathway being able to regulate the number and size of melanin spots in elytra has been reported in H. axyridis ( Zhang et al, 2020 ; Zhang et al, 2021 ).…”
Section: Introductionsupporting
confidence: 67%
“…In our previous study, suppression of the expression level of dopa decarboxylase ( DDC ) also resulted in a melanin-absent phenotype, which is the crucial gene in dopamine melanin synthesis. Even though the melanin disappeared in the elytra in H. axyridis , we can easily discern the characteristic of color pattern because of the original melanin area transforming into a light-yellow color when HaDDC was suppressed ( Xiao et al, 2020 ; Chen et al, 2019b ). However, we did not discern the color pattern in H. axyridis when HaPnr was suppressed in the fourth instar larvae or one-day-old pupae due to the whole elytra represent the same yellow color ( Figures 4F , 5D ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation